Differential expression of hepatic apurinic/apyrimidinic endonuclease 1, a DNA repair enzyme, in chronic hepatitis - Sumiyoshi, Shinichi (Baishideng Publishing Group Co., Limited, 2013)
AIM: To determine hepatic expression of apurinic/apyrimidinic endonuclease 1 (APE-1) and 8-hydroxydeoxyguanosine (8-OHdG) in patients with chronic hepatitis B and C. METHODS: Liver biopsies were obtained from 27 patients with chronic hepatitis B virus (HBV), 30 with chronic hepatitis C virus (HCV), 6 with autoimmune hepatitis (AIH), and 6 with primary biliary cirrhosis (PBC). Normal liver tissue was obtained from surgical resection specimens of four patients. Hepatic APE-1 protein and mRNA expression were assayed by Western blot and by real-time polymerase chain reaction, respectively. Hepatocellular APE-1 and 8-OHdG expression were determined by immunohistochemistry. RESULTS: The staining intensity of hepatocellular nuclear APE-1 was lower in the HBV group than in the other groups (P < 0.05). Hepatic APE-1 protein levels were reduced in the HBV group relative to the other groups. Hepatic APE-1 mRNA levels were also lower in the HBV group. The proportion of hepatocytes with 8-OHdG-positive nuclei was increased in the HCV, AIH and PBC groups (P < 0.05), but not in the HBV group. Hepatocellular nuclear APE-1 levels were positively correlated with hepatocellular 8-OHdG levels in both the HBV and HCV groups (HBV, r = 0.34, P < 0.05; HCV, r = 0.54, P < 0.01). CONCLUSION: An imbalance between oxidative DNA damage and APE-1 expression may contribute to hepatocarcinogenesis in chronic viral hepatitis.